Potensi Pasir Laut dan Agregat Kasar Desa Pasir Putih di Kecamatan Obi Utara sebagai Bahan Beton: The Use of Sea Sand and Coarse Aggregate in Pasir Putih Village at North Obi District as Concrete Materials - La Ani, Nindi; Frans, Pieter Lourens; Apalem, Delvia Rimesye (Litera Academica Publishing, 2024)
The purpose of this study is to investigate whether the use of sea sand as a substitute for river sand in concrete mixtures is an effective common practice. Because of the abundance of sea sand in coastal areas, local residents have successfully used it in a variety of construction applications, including mortar, concrete, and plaster on many types of buildings. To investigate the potential use of sea sand as a substitute for river sand in concrete production, with a focus on determining the strength of the resulting concrete. In addition to sea sand, this study addresses the usage of local coarse aggregates, specifically mountain gravel, which is a key component in concrete mixtures. The availability of sea sand and mountain gravel as major construction resources is expected to support rising housing demand and population growth, particularly in Pasir Putih Village, North Obi District. SNI-03-2834-2000 is the procedure for developing concrete mixture designs and conducting laboratory test experiments. The conclusion reached Sea sand and coarse aggregates from Pasir Putih Village, Obi Utara District, can be used in concrete mixtures, though there are some inconsistencies with SNI specifications, and the compressive strength of concrete produced using sea sand and coarse aggregates from Pasir Putih Village is 10.76 MPa at 7 days and 12.17 MPa at 14 days. The compressive strength at 28 days for the 7-day concrete age is 12.22 MPa, while for the 14-day concrete age it is 13.83 MPa.